2020
DOI: 10.1038/s41379-020-0560-x
|View full text |Cite
|
Sign up to set email alerts
|

KRAS amplification in metastatic colon cancer is associated with a history of inflammatory bowel disease and may confer resistance to anti-EGFR therapy

Abstract: Mutations in RAS occur in 30–50% of metastatic colorectal carcinomas (mCRCs) and correlate with resistance to anti-EGFR therapy. Consequently, mCRC biomarker guidelines state RAS mutational testing should be performed when considering EGFR inhibitor treatment. However, a small subset of mCRCs are reported to harbor RAS amplification. In order to elucidate the clinicopathologic features and anti-EGFR treatment response associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Another retrospective study by Favazza et al (11) reported that all eight patients with KRASamplified mCRC showed disease progression at the time of anti-EGFR therapy, and they concluded that KRAS amplification is responsible for the primary resistance to EGFR inhibitors. Meanwhile, RAS amplifications (involving KRAS, NRAS, and HRAS) were correlated with a younger median patient age at initial diagnosis and a history of inflammatory bowel disease (11). In the present case, KRAS amplification was present before chemotherapy, resulting in resistance to cetuximab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective study by Favazza et al (11) reported that all eight patients with KRASamplified mCRC showed disease progression at the time of anti-EGFR therapy, and they concluded that KRAS amplification is responsible for the primary resistance to EGFR inhibitors. Meanwhile, RAS amplifications (involving KRAS, NRAS, and HRAS) were correlated with a younger median patient age at initial diagnosis and a history of inflammatory bowel disease (11). In the present case, KRAS amplification was present before chemotherapy, resulting in resistance to cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…KRAS amplification in CRC is a rare event, with an overall prevalence of 0.67–2% ( 11 , 12 ). Previous studies have identified somatic mutations in KRAS as biomarkers for inherent resistance to EGFR-targeted drugs in patients with CRC ( 13 ), with a positive tissue mutation rate of 32–52.1% ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…KRAS is part of the RAS/MAPK pathway, a signalling pathway that plays a prominent role in cell proliferation and differentiation. This oncogene has long been found to be mutated, and more recently, amplified, in various types of human cancers, such as colorectal and lung cancer [35][36][37][38][39][40]. Even though RAS mutations are rare in human HCC, RAS activation occurs despite the absence of its mutation [41].…”
Section: Constitutive Oncogene Expression Modelmentioning
confidence: 99%
“…The mutual exclusivity of EGFR amplification and KRAS mutations has been described in lung adenocarcinoma and colorectal carcinoma (CRC) and co-expression caused cytotoxic effect on cells 39 , 40 . Even though the incidence of KRAS amplification compared to its mutation is low, such as less than10% of patients with gastric cancer or CRC and 17% in EAC, clinical features of patients with KRAS amplification are distinct, and the amplification is usually associated with poor prognosis in these patients 41 44 . The oncogenic effect of wild type KRAS amplification is mediated through the increased receptor tyrosine kinase-dependent activation of the Ras pathway in CRC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Like in gastric cancer, EAC, and CRC patients, KRAS amplification is associated with worse survival in ESCC patients 38 . Similar to mutant KRAS , wild type KRAS amplification confers EGFR inhibitor resistance 41 . Therefore, ESCC patients may benefit from detailed EGFR profiling and determination of tumor KRAS amplification status before targeted therapies.…”
Section: Discussionmentioning
confidence: 99%